Anti-ELAB Movement, National Security Law, and heterogeneous institutional trust in Hong Kong. (December 2021) - Tung, Hans H.; Lin, Ming-Jen; Lin, Yi-Fan
Abstract: How does repression on opposition protests affect citizens' institutional trust under dictatorships? There has been a burgeoning literature investigating empirically both long- and short-term impacts of protests and their repression on citizens' political preferences in both democratic and nondemocratic contexts. Yet, the literature tells us relatively little about how the above question could be answered. This paper tries to answer this question by taking advantage of a recent natural experiment in Hong Kong when Beijing suddenly adopted the National Security Law (NSL) in June 2020 to repress dissidents' protest mobilization. Our findings are twofold. First of all, the NSL drove a wedge in the Hong Kong society by making the pro-establishment camp more satisfied with the post-NSL institutions on the one hand, while alienating the pro-democracy camp who lost tremendous trust in them on the other. Second, our study also reveals that one's trust in institutions is significantly associated with the regimes' ability to curb protesters' contentious mobilization. The Hong Kongers who had higher confidence in the NSL to rein in protests would also have a greater level of trust than those who didn't. The effect, however, is substantially smaller among pro-democracy Hong Kongers except for their trust in monitoring institutions. As Beijing is transforming Hong Kong's current institutions from within hopes of bringing about a new political equilibrium, our study helps provide a timely assessment of Hong Kong's institutional landscape and sheds light on how likely this strategy can work.